LEARNING TRANSFORMATION: TEACHERS AND THE DYNAMICS OF ARTIFICIAL INTELLIGENCE (AI) - Nuruddaroini, M. Ahim Sulthan; Abdullah, Moh.; Abdurrohim, Abdurrohim; Muhammad, Farhad; Fitriani, Ely; Fadlillah, Nilna (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to reveal and analyze aboutthe future of teachers with Artificial Intelligence (AI), harmony between teachers and Artificial Intelligence (AI) and teacher competence in dealing with Artificial Intelligence (AI). This research method is qualitative research with a library research approach. The data source in this article is research results in the form of journal articles. The research results show that the presence of artificial intelligence (AI) in education brings challenges and opportunities for the future of teachers. Even though AI can replace some routine tasks in learning, the teacher's role remains crucial in guiding, motivating and developing students holistically. Teachers in the future must be able to build an atmosphere that meets the psychological needs of students, including the need for competence, autonomy and involvement in groups. The introduction of artificial intelligence brings about a significant change in the educational paradigm, where personalization of learning becomes more possible and efficient. Even though there is a paradigm shift from a one-size-fits-all model to responsive adaptation, the teacher's role remains central in designing targeted learning strategies. The success of teachers in the future depends not only on mastery of technology, but also on the ability to guide, motivate and shape students' character. Teachers are also faced with the task of facing the Industry 4.0 revolution, requiring a deep understanding of new concepts such as artificial intelligence, IoT and big data. Efforts to increase teacher competency must involve selective recruitment, bottom-up competency improvement, and the application of technology in learning, such as blended learning. Even though technology plays an important role, teachers cannot be replaced because their role as character builders and facilitators of social interaction remains irreplaceable. Therefore, continuing to develop teacher competence is the key to overcoming educational challenges in the era of artificial intelligence.